PROBLEM OF EQUALITY IN SOCIAL PHILOSOPHICAL STUDIES OF XVI-XVIII cc. - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the analysis of ideas of prominent representatives of Western European social and philosophical thought of the Renaissance and the Enlightenment on equality issue